A Comprehensive Analysis of cis-Acting RNA Elements in the SARS-CoV-2 Genome by a Bioinformatics Approach - Ahmed, Firoz; Sharma, Monika; Al-Ghamdi, Abdulsalam Abdullah; Al-Yami, Sultan Muhammad; Al-Salami, Abdulaziz Musa; Refai, Mohammed Y.; Warsi, Mohiuddin Khan; Howladar, Saad M.; Baeshen, Mohammed N. (Frontiers in Genetics, 2020)
The emergence of a new coronavirus (CoV), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for severe respiratory disease in humans termed as coronavirus disease of 2019 (COVID-19), became a new global threat for health and economy. The SARS-CoV-2 genome is about 29,800 nucleotide long plus-strand RNA that could form functionally important secondary and higher-order structures called cis-acting RNA elements. These elements could interact with viral proteins, host proteins, or other RNAs; and involve in regulating translation and replication processes of the viral genome and encapsidation of the virus. However, the cis-acting RNA elements and their biological roles in SARS-CoV-2 and their comparative analysis in the closely related viral genome have not been well explored, which is very important to understand the molecular mechanism of viral infection and pathogenies. In this study, we used a bioinformatics approach to identify the cis-acting RNA elements in the SARS-CoV-2 genome. Initially, we have aligned the full genomic sequence of six different CoVs, and a phylogenetic analysis was performed to understand their evolutionary relationship. Next, we predicted the cis-acting RNA elements in the SARS-CoV-2 genome using the structRNAfinder tool. Then, we annotated the location of these cis-acting RNA elements in different genomic regions of SARS-CoV-2. After that, we analyzed the sequence conservation patterns of each cis-acting RNA element among six CoVs. Finally, the presence of cis-acting RNA elements across different CoVs genome and their comparative analysis was performed. Our study identified 12 important cis-acting RNA elements in the SARS-CoV-2 genome; among them, Corona_FSE, Corona_pk3, and s2m are highly conserved across most of the studied CoVs; while Thr_leader, MAT2A_D, and MS2 are uniquely present in SARS-CoV-2. These RNA structure elements could involve in viral translation, replication, and encapsidation and, therefore could be potential targets for better treatment of COVID-19. It is imperative to further characterize these cis-acting RNA elements experimentally for a better mechanistic understanding of SARS-CoV-2 infection and therapeutic intervention.